2023
DOI: 10.3390/ani13030336
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles in the Gonads of Red King Crab (Paralithodes camtschaticus) from the Barents Sea

Abstract: Red king crab (Paralithodes camtschaticus) is a large shelf species native to the Pacific Ocean. Due to its high commercial value, this species was introduced into the Barents Sea, where it has formed a new population that now supports a stable commercial fishery. Information on fatty acid profiles in different tissues of the Barents Sea P. camtschaticus is scarce. For this reason, the gonads of red king crabs collected at a coastal site in the Barents Sea during the summer were analyzed for fatty acid composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The differences in the fatty acid content among individuals of different sizes may be attributed not only to size but also to the maturity stage of the gonads and the physiological state [ 50 ]. For example, Dvoretsky et al [ 51 ] reported that the size of female red king crabs ( Paralithodes camtschaticus ) did not affect the fatty acid content in their edible parts, which is consistent with the findings of Ying et al [ 42 ] on Chinese mitten crabs. When evaluating the ratio of PUFA to SFA fatty acids, it was found that the most favorable ratio in nutritional terms characterized gonadal lipids: 1.74 and 1.64 (small and large females, respectively), while the least favorable ratio was for hepatopancreas lipids, which, depending on sex and size, was between 0.91 and 1.19.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The differences in the fatty acid content among individuals of different sizes may be attributed not only to size but also to the maturity stage of the gonads and the physiological state [ 50 ]. For example, Dvoretsky et al [ 51 ] reported that the size of female red king crabs ( Paralithodes camtschaticus ) did not affect the fatty acid content in their edible parts, which is consistent with the findings of Ying et al [ 42 ] on Chinese mitten crabs. When evaluating the ratio of PUFA to SFA fatty acids, it was found that the most favorable ratio in nutritional terms characterized gonadal lipids: 1.74 and 1.64 (small and large females, respectively), while the least favorable ratio was for hepatopancreas lipids, which, depending on sex and size, was between 0.91 and 1.19.…”
Section: Discussionsupporting
confidence: 73%
“…These values are considerably lower compared to various species of marine crabs. For example, according to Dvoretsky et al [ 51 ], the n-3 to n-6 PUFA ratio in the gonads of red king crabs from the Barents Sea exceeds 4. When comparing these values to Chinese aquaculture crabs, the ratio ranged from 0.5 in crabs fed with frozen waste to 1.1 in those fed with formulated feed [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pearson correlation coefficients were calculated for log-transformed data to identify potential associations between fatty acid content in the eggs and ovaries of red king crabs. Ovary fatty acid content data for the same females used in the egg fatty acid analysis were extracted from our previous publication [19]. Statistical analyses were carried out using NCSS PASS 2004 and PAST 3.26.…”
Section: Methodsmentioning
confidence: 99%
“…Important by-products, such as the hepatopancreas [15] and shell [16], are used for the production of chitin, chitosan, α-glucosidase inhibitors, and the anticancer agent prodigiosin, as well as proteolytic enzymes and non-protein components such as essential fatty acids [17]. Recently, the fatty acid composition of other by-products, such as hemolymph and heart muscles, which are currently discarded at sea after standard onboard processing, has also been investigated [18,19].…”
Section: Introductionmentioning
confidence: 99%